Role of interleukin 4 and its receptor in clinical presentation of chronic extrinsic allergic alveolitis: a pilot study - Sterclova, Martina; Matej, Radoslav; Mandakova, Petra; Skibova, Jelena; Vasakova, Martina (Multidisciplinary respiratory medicine, 2013)
BACKGROUND: Th-2 cytokine milieu including interleukin 4 (IL-4) was detected in fibrotic lung diseases. Chronic extrinsic allergic alveolitis (EAA) may be also accompanied by marked fibrogenesis. The aim of this study was to determine if IL-4 and its receptor (IL-4R-alpha) play any role in the clinical presentation and pathogenesis of chronic EAA. METHODS: Twenty patients originally investigated for interstitial lung disease and finally diagnosed affected with chronic EAA and sarcoidosis were prospectively enrolled into the study. Concentrations of IL-4, IL-4R-aplha and total protein were assessed in the bronchoalveolar lavage fluid (BALF) of all enrolled subjects as well as high resolution computed tomography (HRCT) scores and pulmonary function tests. RESULTS: BALF IL-4R-alpha and total protein concentrations were significantly higher in chronic EAA patients (p < 0.05). Concentrations of BALF IL-4R-alpha were significantly higher in men than in women (p < 0.05) in EAA group. Total protein BALF levels were significantly elevated in ex-smokers with EAA compared to nonsmokers (p < 0.05). A positive correlation (p < 0.01) between IL-4R-alpha BALF concentrations and HRCT interstitial scores were observed in chronic EAA group; the IL-4R-alpha/total protein ratio showed the same significant positive correlation. A negative correlation between lung function results and IL-4R-alpha, and IL-4R-alpha/total protein as well, was also found (p < 0.05). CONCLUSIONS: We suggest a clinical relevance for the IL-4/IL-4R axis in the etiopathogenesis of chronic EAA. IL-4R-alpha could serve as a potential biomarker of lung fibrogenesis.